Integration of mobile augmented reality (MAR) applications into biology laboratory: Anatomic structure of the heart - Cuneyd Celik; Gokhan Guven; Nevin Kozcu Cakir (Association for Learning Technology, 2020)
The purpose of the current study is to design and develop a sample Mobile Augmented Reality (MAR) application addressing the anatomic structure of the heart in a way suitable for laboratory learning for pre-service science teachers to achieve learning by constructing information in biology instruction. The implementation of the MAR design activity was conducted with the participation of 30 pre-service teachers taking the biology laboratory course. The implementation process of the activity consists of four stages. The first stage includes the introduction of the MAR application program and marker; the second stage includes the use of the MAR application in a laboratory environment; the third stage includes the operation of dissection and the last stage includes the association of the MAR application with the operation of dissection and general evaluation. Then, semi-structured interviews were conducted by involving pre-service teachers and the data obtained from these interviews revealed that integration of heart dissection with MAR application helped the pre-service teachers to better understand the anatomic structure of the heart and the related concepts. Thus, a sample activity demonstrating how MAR, which is an instructional method with strong potential for reification and visualisation, can be integrated into the teaching of concepts in laboratory settings was developed.